A Comunity Empowerment of Comunity Reading Park /Taman Baca Masyarakat Dungus Biuk (Rubadubi) through the Literacy Movement - Giyanti, Ummu Ahya; Waode Asma Binti Laode Agus Salim (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2024)
This research aims to determine the process of community empowerment in Babakan village, Tenjo, Bogor by Community Reading Park (TBM) of Dungus Biuk Reading House (Rubadubi) through Literacy Movement. The research method used is qualitative descriptive. The results of the study show that the Community Reading Park (TBM) of the Dungus Biuk Reading House (Rubadubi) Babakan Village, Tenjo District, Bogor Regency is a community reading park engaged in non-formal education and social society. There are three stages of the process of community empowerment through the literacy movement, namely: (1) The stage of awareness and behavior formation, by providing guidance and counseling through literacy activities to the community to participate in the TBM Rubadubi program. (2) The stage of the process of transforming knowledge and skills, the implementation of the TBM Rubadubi program and training skills through innovative literacy activities. (3) The stage of improving intellectual ability and proficiency, there is an increase in achievement and courage in literacy. It can be concluded that community empowerment in the object of research has been carried out effectively through services, facilities, guidance, and activity programs that have been provided. This can be seen from the condition of the community before TBM Rubadubi, children tend not to continue their junior high school/high school education because they choose to work, after TBM Rubadubi and children participate in activity programs to increase insight and knowledge so that they are aware of the importance of education.